2004
DOI: 10.1016/j.ejcts.2004.08.020
|View full text |Cite
|
Sign up to set email alerts
|

?Tamponade? following cardiac surgery: terminology and echocardiography may both mislead

Abstract: Haemodynamically significant pericardial collections occurring early following cardiac surgery rarely cause classical clinical or echocardiographic features of tamponade. Recognition of this as a separate diagnostic entity is necessary to ensure appropriate surgical intervention is not delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 14 publications
2
80
1
1
Order By: Relevance
“…[5] In addition, it has been suggested that TEE provides more valuable information in cases of localized tamponade and that it may reveal some additional findings that cannot be seen via TTE. [23,24] This may be supported by the results of İmren et al [13] in which TTE had a 60% false negativity rate (almost the same as the findings of our study and those of Price et al [9] ). However, they based their diagnostic confirmation on the results of TEE results since their surgical results were highly concordant with the TEE findings.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…[5] In addition, it has been suggested that TEE provides more valuable information in cases of localized tamponade and that it may reveal some additional findings that cannot be seen via TTE. [23,24] This may be supported by the results of İmren et al [13] in which TTE had a 60% false negativity rate (almost the same as the findings of our study and those of Price et al [9] ). However, they based their diagnostic confirmation on the results of TEE results since their surgical results were highly concordant with the TEE findings.…”
Section: Discussionsupporting
confidence: 82%
“…[4] A number of previous studies have focused on trying to determine to what extent echocardiographic evaluations provide reliable information in the diagnosis of postoperative cardiac tamponade. For example, Price et al [9] seem to have been the first to analytically describe the limited capability of echocardiography in the diagnosis of this condition. In their study, they divided the patients into two groups according to the time of revision and reported that there were no classic echocardiographic features of tamponade in up to 80% of the patients within the first 72 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main complications of PPS are development of tamponade and constrictive pericarditis (1)(2)(3)(4)(5)(6). Tamponade complicates PPS in 6.4% and constrictive pericarditis in 2-3% of patients (11,12). We aimed to summarize current evidence on prevalence, clinical significance, outcomes and management of postpericardiotomy syndrome developing after cardiac surgery and its complications -tamponade and constrictive pericarditis.…”
Section: Introductionmentioning
confidence: 99%